Plasma acidosis and peak power after a supramaximal trial in elite sprint and endurance cyclists: effect of bicarbonate - Mildenhall, M.; Maunder, E.; Plews, D. J.; Lindinger, M. I.; Cairns, S. P. (Medicine & Science in Sports & Exercise, 2023)
Purpose This study aimed to determine whether (i) a plasma acidosis contributes to a reduction of mechanical performance and (ii) bicarbonate supplementation blunts plasma acidosis and arterial oxygen desaturation to resist fatigue during the end spurt of a supramaximal trial in elite sprint and endurance cyclists.